Validity of the interview script of Educational Practices for teachers (RE-HSE-PR) - Bolsoni-Silva, Alessandra Turini [UNESP]; Barbosa Oliveira, José Egídio; Loureiro, Sonia Regina (My University, 2019)
In the school context, social skills in teachers and children, as well as child behavioral problems, contribute to the social development and learning of the students, however, there is no instrument that evaluates these variables in an integrated way. Therefore, the aim was to investigate the validation of the Interview Script of Educational Practices for Teachers (RE-HSE-Pr) instrument. The RE-HSE-Pr was developed in a similar way to other pre-existing instruments in which parents are the information source. After validation, it had 9 guide-questions organized on three information axes: Communication, Affection and Establishment of Limits. Participants were teachers of 283 pre-school and school age children, who answered both the RE-HSE-Pr and Teacher's Report Form (TRF). Evaluations of the construct and discriminant validity and reliability were performed, according to technical procedures. Two factors with adequate alpha (positive total; negative total) were identified, and discriminant analyses discriminated cases from non-cases; boys from girls and pre-school children from school children. Psychometric indicators were satisfactory.
Validação do Roteiro de Entrevista de Práticas Educativas para Professores (RE-HSE-Pr)
Keywords: Behavior problems; Educational practices; Educational social skills; School; Social skills